Key policies for addressing the social determinants of health and health inequities - Saunders, Matthew (Public health registrar); Barr, Ben (Benjamin); McHale, Phil; Hamelmann, Christoph (Health Evidence Network synthesis report., 2017)
Evidence indicates that actions within four main themes (early child development, fair employment and decent work, social protection, and the living environment) are likely to have the greatest impact on the social determinants of health and health inequities. A systematic search and analysis of recommendations and policy guidelines from intergovernmental organizations and international bodies identified practical policy options for action on social determinants within these four themes. Policy options focused on early childhood education and care; child poverty; investment strategies for an inclusive economy; active labour market programmes; working conditions; social cash transfers; affordable housing; and planning and regulatory mechanisms to improve air quality and mitigate climate change. Applying combinations of these policy options alongside effective governance for health equity should enable WHO European Region Member States to reduce health inequities and synergize efforts to achieve the United Nations Sustainable Development Goals.